Genetic differences between Japan and other countries in cyp51A polymorphisms of Aspergillus fumigatus. Issue 11 (29th September 2021) - Majima, Hidetaka; Arai, Teppei; Kusuya, Yoko; Takahashi, Hiroki; Watanabe, Akira; Miyazaki, Yasunari; Kamei, Katsuhiko
Abstract: Background: Mutations in cyp51A gene are known as main mechanisms of azole resistance in Aspergillus fumigatus, whereas azole‐susceptible strains also carry cyp51A mutations (polymorphisms). The polymorphisms found in Europe mainly consist of two combinations of mutations, that is combinations of five single‐nucleotide polymorphisms (SNPs) of cyp51A, referred to as cyp51A ‐5SNPs, and combinations of three SNPs of cyp51A, referred to as cyp51A ‐3SNPs. Few studies have compared the distributions of cyp51A polymorphisms between different regions. Objectives: The aim of this study was to investigate the regional differences of cyp51A polymorphisms. Methods: We compared the proportions of cyp51A polymorphisms in clinical and environmental strains isolated in various countries, and analysed the strains phylogenetically using short tandem repeats (STRs) and whole‐genome sequence (WGS). Results: Among the Japanese strains, 15 out of 98 (15.3%) clinical strains and 8 out of 95 (8.4%) environmental strains had cyp51A polymorphisms. A mutation of cyp51A N248K was the most prevalent polymorphism in both clinical ( n = 14, 14.3%) and environmental strains ( n = 3, 3.2%). Only one environmental strain harboured cyp51A ‐5SNPs, which was reported to be the most prevalent in Europe. For phylogenetic analyses using STRs and WGS, 183 and 134 strains, respectively, were employed. They showed that most of the strains with cyp51A N248K clustered in the clades different from those of the strains with cyp51A ‐5SNPs and cyp51A ‐3SNPs as well as from those with TR34 /L98H mutations. Conclusions: This study suggests that there are genetic differences between cyp51A polymorphisms of A . fumigatus in Japan and Europe.